#MadelungDeformity: Insights Into a Rare Congenital Difference Using Social Media. (March 2023) - Peymani, Abbas; Lokhorst, Max M.; Chen, Austin D.; van der Horst, Chantal M.A.M.; Lee, Bernard T.; Lin, Samuel J.; Strackee, Simon D.
Background: Madelung deformity is a rare congenital hand difference with little known regarding the patient perspective. In this cross-sectional survey study, we harnessed the global reach of social media to understand the clinical spectrum of Madelung deformity and its impact on physical, mental, and social health. Methods: A survey was developed based on a previously published protocol and multiple Patient-Reported Outcomes Measurement Information System (PROMIS) short forms. The survey was distributed on several Madelung deformity communities on Facebook and Instagram. T -scores were calculated, interpreted, and compared between patients who underwent surgery and those who did not. Correlations between scores were calculated using the Spearman rank correlation coefficient. Results: Mean PROMIS scores for adults were as follows: pain intensity, 4.9 ± 2.8; pain interference, 57.6 ± 10.0; upper extremity, 35.2 ± 8.1; depression, 53.8 ± 11.1; anxiety, 55.4 ± 11.4; and ability to participate in social roles and activities, 42.5 ± 7.7. Mean scores for children were as follows: pain intensity, 5.0 ± 2.8; pain interference, 55.7 ± 11.3; upper extremity function, 24.6 ± 10.4; depressive symptoms, 57.7 ± 11.3; anxiety, 57.3 ± 11.9; and peer relationships, 42.2 ± 10.3. Conclusions: Madelung deformity has significant effects on patients' physical, mental, and social well-being, even after surgical treatment. Using social media, we were able to compensate for Madelung deformity's rarity by engaging an international audience, demonstrating the feasibility to conduct research through it, and providing a global perspective of the disease entity.